2016
DOI: 10.1371/journal.ppat.1005718
|View full text |Cite
|
Sign up to set email alerts
|

An Epstein-Barr Virus-Encoded Protein Complex Requires an Origin of Lytic Replication In Cis to Mediate Late Gene Transcription

Abstract: Epstein-Barr virus lytic replication is accomplished by an intricate cascade of gene expression that integrates viral DNA replication and structural protein synthesis. Most genes encoding structural proteins exhibit “true” late kinetics–their expression is strictly dependent on lytic DNA replication. Recently, the EBV BcRF1 gene was reported to encode a TATA box binding protein homolog, which preferentially recognizes the TATT sequence found in true late gene promoters. BcRF1 is one of seven EBV genes with hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 69 publications
5
72
2
Order By: Relevance
“…The Tp1 cluster contains multiple members of the EBV viral preinitiation complex, which activates expression of most EBV late genes from newly replicated viral DNA (Aubry et al., 2014, Djavadian et al., 2016). The Tp2 cluster included proteins important in inhibition of host innate immunity, and multiple tegument, capsid, and envelope proteins were present in the later-expressed Tp3 class.…”
Section: Resultsmentioning
confidence: 99%
“…The Tp1 cluster contains multiple members of the EBV viral preinitiation complex, which activates expression of most EBV late genes from newly replicated viral DNA (Aubry et al., 2014, Djavadian et al., 2016). The Tp2 cluster included proteins important in inhibition of host innate immunity, and multiple tegument, capsid, and envelope proteins were present in the later-expressed Tp3 class.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the late gene expression defect of the ORF18 E36A_L37A mutant is exacerbated in the context of the virus, compared to in the plasmid promoter activation assay, likely reflects the fact that the plasmid assay measures basal promoter activation but misses other regulatory components of this cascade. For example, the origin of lytic replication is required in cis for late gene expression in related gammaherpesviruses (3, 28) and the reporter assay does not capture the important contribution of viral DNA replication towards late gene expression. This may explain why some mutants that are defective for ORF30 binding (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are: BcRF1, BDLF3.5, BDLF4, BFRF2, and BVLF1. Knockout of BcRF1, BDLF4, BVLF1, BDLF3.5 and BFRF2 disrupts expression of late genes [1114]. However, the exact function of several of these late gene regulators is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…HCMV UL79, the ortholog of EBV BVLF1, functions as an elongation factor of RNAPII during the late phase of viral gene expression [20]. Sub-nuclear localization studies revealed that late gene regulators assemble in replication compartments and that true late genes are transcribed from newly replicated viral DNA [14, 21, 22]. Formation of replication compartments might increase the local concentration of these late gene regulators and promote their interaction with replication proteins to stimulate synthesis of late transcripts.…”
Section: Introductionmentioning
confidence: 99%